A 6-Month Follow-up Case Study of Low-Frequency Right Prefrontal Repetitive Transcranial Magnetic Stimulation in Treatment-Resistant Bipolar Depression. Issue 4 (December 2017) - Kito, Shinsuke; Matsuda, Yuki; Sewaki, Yurie; Sekiya, Junpei; Fujii, Takeshi; Noda, Takamasa; Ikezawa, Satoru; Takano, Harumasa; Nakazawa, Kanako; Nomura, Mami; Setoyama, Shiori; Nakagome, Kazuyuki
Abstract : Supplemental digital content is available in the text.